2019
DOI: 10.3390/catal9080682
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Pyrolysis Processes of Ce-MOFs for Preparing Highly Active Catalysts of Toluene Combustion

Abstract: Metal organic frameworks (MOFs) have recently been used as precursors of the catalysts for the combustion of volatile organic compounds (VOCs). In the present work, three kinds of CeO 2 catalysts were successfully synthesized from Ce-MOF-808, Ce-BTC, and Ce-UiO-66, with specific topological structures and coordinate environments. Catalysts with small particle size, stacking mode, and structural defects could be created by pyrolysis of Ce-MOFs, which affects the activity in the toluene combustion significantly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…The overall catalytic performance results showed that the samples with the most surface reactive oxygen species had the best catalytic activity. With the incorporation of Cu, the T 90 of Cu-CeO x -MOF-n declined obviously and the catalytic activity under high conversion enhanced significantly in comparison to CeO 2 -MOF-808, whose T 90 was tested 278 • C in our previous stage of work [22]. In addition, the Cu-CeO x -MOF-0.2 catalysts had decent catalytic expression under different WHSVs (Figure 7b).…”
Section: Catalytic Performancementioning
confidence: 87%
See 1 more Smart Citation
“…The overall catalytic performance results showed that the samples with the most surface reactive oxygen species had the best catalytic activity. With the incorporation of Cu, the T 90 of Cu-CeO x -MOF-n declined obviously and the catalytic activity under high conversion enhanced significantly in comparison to CeO 2 -MOF-808, whose T 90 was tested 278 • C in our previous stage of work [22]. In addition, the Cu-CeO x -MOF-0.2 catalysts had decent catalytic expression under different WHSVs (Figure 7b).…”
Section: Catalytic Performancementioning
confidence: 87%
“…In our previous work, Ce-MOF-808 with three-dimensional porous structure was used as the precursor to prepare the CeO 2 catalyst. The prepared CeO 2 -MOF-808 with large specific surface area and abundant active sites showed good catalytic performance [19,22]. The uniformity of metal-organic frameworks (MOFs) [23,24] provides the possibility for highly dispersed introduction of Cu [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the stage between 100 C and 320 C, all the samples undergo slow decomposition of MOF-808, releasing coordinated water, DMF solvent molecules and formic acid ligands. 27 The weight losses at this stage are about 20%, 14%, 9% and 6% for MOF-808, 808-PVDF0.7, 808-PVDF0.5 and 808-PVDF0.3, respectively. Because there is almost no weight loss for pure PVDF polymers before 400 C, 28 we could calculate that the contents of MOF-808 in 808-PVDFx are about 70%, 45% and 30% for 808-PVDF0.7, 808-PVDF0.5 and 808-PVDF0.3, respectively.…”
Section: Characterization Of Mof-808 Beadsmentioning
confidence: 93%
“…The Ce-based MOFs were treated as precursors to obtain CeO 2 catalysts for effective degradation of 4-nitrophenol, toluene, o-xylene, and dyes (Figure 6). [107][108][109][110] The prepared CeO 2 -based catalysts from MOF materials can maintain the general morphology and realize the effective reduction/ oxidation of organic pollutions. The porous structure of MOFs can effectively enhance the catalytic activity of obtained CeO 2 catalysts, which can effectively degrade these organic pollutions.…”
Section: Organics Degradationmentioning
confidence: 99%